Putting the Private Sector on Track - World Bank (Washington, DC, 2012)
The Regional Program on Enterprise Development (RPED) is designed to examine what specific factors hinder enterprise development in Africa and what can be done to mitigate them. RPED is a research initiative which will collect and analyze a large, varied, and unique set of data. RPED focuses on four manufacturing sectors (textile and garment, food, woodworking, and metalworking) in nine countries (Cameroon, Cote d'Ivoire, Ghana, Kenya, Burundi, and Rwanda are treated as one data set. Tanzania, Zambia, and Zimbabwe are the other countries involved). The principal objectives of RPED's research program are: 1) to develop a more precise understanding of how various elements of the African business environment influence private enterprise behavior and performance. 2) To translate the research results into recommendations for more effective policies and assistance programs for private enterprise development. 3) To strengthen the analytic capacity of African institutions. 4) To create the capability for both donor agencies and African institutions in the private enterprsie development field to monitor trends and developments in industrial activity. RPED will focus on regulatory polies, the principal determinants of transaction costs, business support agents, the factors that contribute to or hinder the acquisition of technological capability, and firms' ressponses to infrastructure deficiencies.